Silages containing bioactive forage legumes: a promising protein‐rich feed source for growing lambs. (2nd May 2016) - Copani, G.; Niderkorn, V.; Anglard, F.; Quereuil, A.; Ginane, C.
Abstract: Forage legumes that contain secondary compounds are considered to be less susceptible to proteolysis than other legumes, with improved silage quality and possibly improved animal performance. This was investigated feeding five groups of growing lambs for 10 weeks, five silages composed of pure timothy (T; Phleum pratense ), mixtures of T with red clover ( Trifolium pratense ; T‐RC, 50/50 on DM basis), sainfoin ( Onobrychis viciifolia ; T‐SF), or both (T‐RC‐SF, 50/25/25), or a mixture of the two legumes (RC‐SF). Including SF and/or RC in silages improved silage fermentation as shown by higher lactic acid and lower soluble N and NH3 contents than in T silage. Voluntary intakes were higher with all the RC‐containing silages than with T and T‐SF. The T‐SF silage had the lowest, and RC‐containing silages the highest average values for daily gain, feed conversion efficiency, live weight and carcass weight. The differing effects of these silages cannot be totally explained by differences in their nutritive value and so may be due to their bioactive compounds impacting differently on feeding motivation and digestive efficiency. These results suggest that including RC in silages is a promising strategy to combine improved animal performance with reduced environmental pressure.